Ples s palico - Kašček, Ana (Šport (Ljubljana), 2013)
The knowledge of ballet, gymnastics and dance techniques to different kinds of music with different elements. This is done with a special baton, using highthrows and rolls all over the sportsman's body, either alone, in pairs or in groups. Twirling is all of the above. Although twirling is evolving quite well in Slovenia we still do not have an appropriate Slovenian word. Therefore, we keep using the original, which means to twirl. In 2003 the "Mažoretna zveza Slovenije" (The Slovene Majorettes Federation) changed their name to "Twirling zveza Slovenije" (The Slovene Twirling Federation). There were some clubs which did not want to leave off majorettes, so they were renamed "Mažoretna in Twirling zveza Slovenije" (The Slovenie Majorettes and Twirling Federation). There are already more than 50 clubs, societies and groups in Slovenia and there are even individuals who are trainers and judges.This article introduces the reader to twirling elements and their learning methods. The competition disciplines as well as the compositions are also mentioned in the article.
Keywords: aerials; baton twirling; competitions; contact material; kotaljenja; meti; metodika; metodology; rokovanja; rolls; sport; šport; tekmovanja; twirling